The Profile of Students' Critical Thinking Skills and Potential Learning Media for Grade XII Biotechnology Material to Support SDGs 2 - Amelia Putri, Rischa; Faizah, Ulfi (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
This study aims to describe the profile of critical thinking skills of grade XII students on biotechnology material and analyze the types of alternative learning media that can support the strengthening of these skills in order to support the sustainable development goals (SDGs) point 2 on food security. The method used is descriptive qualitative with a study literature review approach and strengthening field data through learning reflections and teacher interviews. The results of the study indicate that students' critical thinking skills are still in the low category, with the main obstacles lying in the aspects interpretation, explanation, and evaluation. The learning process is still conventional and minimal practice causes students to be less actively involved in higher-order thinking processes. Based on literature analysis and field findings, recommended learning media to develop critical thinking skills include E-modules and E-LKPD. These media are considered capable of facilitating contextual, reflective, and applicable biotechnology learning so that they are relevant to support the achievement of SDGs 2 related to sustainable food security